LEGAL DEPOSIT OF ELECTRONIC PUBLICATIONS IN MALAYSIA: 1988-2000 - Ibrahim, Shahrozat; Edzan, N.N. (Malaysian Journal of Library and Information Science, 2004)
This paper analyses statistical data of non-print/electronic publications received and registered by the National Depository Centre, Perpustakaan Negara Malaysia since the enforcement of the Deposit of Library Material Act, 1986. Out of the 7,926 titles of non-print publications received and registered from 1988 - 2000, only 165 titles (2.08%) are electronic publications. The findings indicate that the types of electronic publications received and registered are limited to off-line electronic publications namely, CD-ROMs, diskettes and computer software. The legal deposit of on-line electronic publications has yet to materialise. The study is supported by interviews with relevant authorities to obtain information regarding issues related to legal deposit of electronic publications in Malaysia such as the ineffectiveness of the current legal deposit legislation, inadequate number of staff handling legal deposit of electronic publications and other non-print material, the public’s unawareness of the importance of legal deposit of electronic publications and the fear of publishers with the legal deposit of their electronic publications.